2008
DOI: 10.2105/ajph.2007.120055
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Metabolic Syndrome Among US Women of Childbearing Age

Abstract: The current trends of metabolic syndrome among women of childbearing age demonstrate the need for additional rigorous investigations regarding its long-term effects in these women and their offspring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
0
4

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(49 citation statements)
references
References 37 publications
4
41
0
4
Order By: Relevance
“…Estimations of the overall prevalence of the metabolic syndrome have demonstrated that rates are comparable between whites, blacks, and Mexican Americans, but when the data are analyzed by gender, some racial disparities become evident. Specifically, black, Hispanic and Mexican American women are more likely to meet the criteria for the metabolic syndrome than white women [38][39][40][41]. Due to the high rate of CV disease-related mortality among patients with the metabolic syndrome [42], treatments for OA that have CV side effects may not be appropriate for use in these patient populations.…”
Section: Racial and Ethnic Disparities In Risk Factors For Nsaid Toximentioning
confidence: 99%
“…Estimations of the overall prevalence of the metabolic syndrome have demonstrated that rates are comparable between whites, blacks, and Mexican Americans, but when the data are analyzed by gender, some racial disparities become evident. Specifically, black, Hispanic and Mexican American women are more likely to meet the criteria for the metabolic syndrome than white women [38][39][40][41]. Due to the high rate of CV disease-related mortality among patients with the metabolic syndrome [42], treatments for OA that have CV side effects may not be appropriate for use in these patient populations.…”
Section: Racial and Ethnic Disparities In Risk Factors For Nsaid Toximentioning
confidence: 99%
“…However, casting gestational diabetes merely as a pregnancy associated complication that mostly resolves after delivery [6,7], is inappropriate in an era where the prevalence of the metabolic syndrome and diabetes itself is increasing in all demographics, including that of women of childbearing age [8,9]. Reflecting this trend, the Standards of Medical Care in Diabetes 2012 not only calls for women with risk factors to be screened for undiagnosed type 2 diabetes at the first prenatal visit, but also defines gestational diabetes as 'diabetes diagnosed during pregnancy that is not clearly overt diabetes [10]; this represents additional precision in the definition of GDM, which as recently as 2009 was defined simply as 'diabetes diagnosed during pregnancy [6].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, in one report only 34% to 74% of women with a history of GDM received the recommended postpartum glucose screening [14]. These missed glucose screening opportunities and lack of effective intervention may be associated with the marked increase seen in the incidence of T2D among women of childbearing age [8,9]. For this cohort of women, pregnancy may represent the first time that they undergo screening for diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…There is also a need for studies to determine whether physical activity recommendations developed from primarily white, male individuals are appropriate for other populations who are at increased risk for chronic disease. We chose to study Hispanic women because of the higher prevalence of central obesity (St-Onge, Janssen, & Heymsfield, 2004), hyperinsulinaemia (Haffner et al, 1990;Ho, Davy, Hickey, Summers, & Melby, 2002), dyslipidaemia (Ramos & Olden, 2008), and increased risk for metabolic syndrome (Ford, Giles, & Mokdad, 2004;Ramos & Olden, 2008) and type 2 diabetes (Stern, Gaskill, Hazuda, Gardner, & Haffner, 1983) relative to non-Hispanic white and non-Hispanic black women of similar age. The main aim of the present study was to compare CVD risk factors in a sample of Hispanic women who meet current guidelines for physical activity against those who do not meet current guidelines using an objective measure of physical activity.…”
Section: Introductionmentioning
confidence: 99%